Which probiotic species or combinations of species are best for treating irritable bowel syndrome?. Issue 5 (May 2016) - Adegoke, Olusola; Satre, Thomas
Abstract : Evidence‐Based Answer : Pooled together, probiotics improve irritable bowel syndrome (IBS) symptoms compared to placebo with an NNT of 7 (SOR: A, meta‐analyses of RCTs). Lactobacillus plantarum and species in the genus Escherichia reduce the risk of persistent symptoms. Streptococcus faecium may also reduce the risk of persistent symptoms. Combination products containing Bifidobacterium infantis, Lactobacillus casei, and Lactobacillus plantarum or Bifidobacterium longum, Lactobacillus acidophilus, Lactobacillus bulgaricus, and Streptococcus salivarius ssp thermophilus decrease distension and flatulence. Products containing Bifidobacterium breve, B longum, or L acidophilus improve abdominal pain, distention, and flatulence (SOR: B, metaanalyses of small RCTs).